Comparison of the Performance of Groundnut Shell-Based Carbon-Reinforced PLA Composites, Fabricated using Injection Molding and Pellet 3D Printing - M. Radhika; B.A. Prasad; S. Akella (Archives of Metallurgy and Materials)
This study intended to investigate the impact of two distinct shaping methods, Injection molding and pellet additive manufacturing, on tensile and thermal properties of PLA based materials. It included comparisons of neat PLA and PLA reinforced with carbon nanoparticles derived from groundnut shells (GNSC) via pyrolysis at 800°C. These nanoparticles were characterized using FTIR, XRD, FESEM, and EDX analyses to assess their carbon content, morphology, and structure. The synthesized carbon was used as a reinforcement filler in the PLA matrix and biobased polymer nanocomposites were prepared by pellet 3D printing and injection molding. The mechanical and thermal characteristics of PLA/GNSC composite specimens with 0.25, 0.5, and 0.75 wt% of GNSC nanoparticles were compared. Reinforcing PLA with GNSC nanoparticles improved tensile properties in both shaping techniques. The PLA/GNSC_0.5 exhibited the greatest tensile strength, measuring 58.61 MPa for injection molded samples and 53.05 MPa for 3D printed samples, representing a 50% enhancement compared with neat PLA. The tensile modulus was also highest for PLA/GNSC_0.5, measuring 1.24 GPa for injection molded samples and 1.21 GPa for 3D printed samples, representing an improvement of 14% compared with neat PLA. The tensile characteristics showed a modest increase in tensile strength (9-13%) and a slight improvement in tensile modulus (2-3%) for injection molded samples compared to 3D printed samples. The thermal properties showed no substantial variation between the two shaping methods. These findings highlight the effectiveness of GNSC nanoparticles in enhancing the mechanical and thermal performance of PLA composites, regardless of the shaping technique.